1998
DOI: 10.3758/bf03201152
|View full text |Cite
|
Sign up to set email alerts
|

Novel popout without novelty

Abstract: Localization of a novel word in an array with several familiar words is typically enhanced relative to localization in an all-novelarray (between-array novel popout) and sometimes enhanced relative to familiar words in one-novel arrays (within-array novel popout), Christie and Klein (1996) have questioned the reality of the latter effect, suggesting that it may be an artifact of guessing bias, The present Experiment 1 replicated within-array novel popout with the novel word probed at chance (i.e., on only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…The conclusion that novelty itselfdoes not account for the novel-popout effect is consistent with the findings of Diliberto et al (1998). Johnston et al (1993, Experiment 4) had previously found a novel-popout effect only if sets of familiarized words were shown repeatedly in the same arrays.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The conclusion that novelty itselfdoes not account for the novel-popout effect is consistent with the findings of Diliberto et al (1998). Johnston et al (1993, Experiment 4) had previously found a novel-popout effect only if sets of familiarized words were shown repeatedly in the same arrays.…”
Section: Discussionsupporting
confidence: 84%
“…Although the results of Diliberto et al (1998) suggest that the interitem associations, not novelty per se, accounts for novel popout, those results are generally consistent with the mismatch theory proposed by Johnston and Hawley (1994). That is, without the mutual lateral excitation of the identity nodes, top-down inhibition of the iconic nodes might be insufficient to suppress perceptual processing ofthe familiar stimuli.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This has been called the novel popout phenomenon (Johnston and Schwarting, 1997;Reicher et al, 1976), and is also believed to rely on attentional processes (Strayer and Johnston, 2000). The reliability of the effect, however, has been questioned and the results have also been explained as effects of cognitive load (for a critical view see Christie and Klein, 1996), or inter-item associations (Diliberto et al, 1998).…”
Section: Attention To Noveltymentioning
confidence: 99%
“…The so-called novel popout effect only occurs in a context containing a group of related items (typically three) and one unique item. This can occur even if the unique item is not differentiated by novelty but only by category, such as not being a tree word among "pine", "oak", and "maple" (Diliberto, Altarriba, & Neill, 1998). The novel popout effect is about novelty as defined by uniqueness in a group.…”
mentioning
confidence: 99%